Determining resident microbial community members and their correlations with geochemistry in a serpentinizing spring - Trutschel, Leah R.; Kruger, Brittany R.; Sackett, Joshua D.; Chadwick, Grayson L.; Rowe, Annette R. (Frontiers in Microbiology, 2023)
Terrestrial serpentinizing systems allow us insight into the realm of alkaliphilic microbial communities driven by geology in a way that is frequently more accessible than their deep subsurface or marine counterparts. However, these systems are also marked by geochemical and microbial community variation due to the interactions of serpentinized fluids with host geology and the surface environment. To separate the transient from the endemic microbes in a hyperalkaline environment, we assessed the Ney Springs terrestrial serpentinizing system microbial community and geochemistry at six time points over the span of a year. Using 16S rRNA gene surveys we observed 93 amplicon sequence variants (ASVs) that were found at every sampling event. This is compared to ~17,000 transient ASVs that were detected only once across the six sampling events. Of the resident community members, 16 of these ASVs were regularly greater than 1% of the community during every sampling period. Additionally, many of these core taxa experienced statistically significant changes in relative abundance with time. Variation in the abundance of some core populations correlated with geochemical variation. For example, members of the Tindallia group, showed a positive correlation with variation in levels of ammonia at the spring. Investigating the metagenome assembled genomes of these microbes revealed evidence of the potential for ammonia generation via Stickland reactions within Tindallia. This observation offers new insight into the origin of high ammonia concentrations (>70 mg/L) seen at this site. Similarly, the abundance of putative sulfur-oxidizing microbes like Thiomicrospira, Halomonas, and a Rhodobacteraceae species could be linked to changes observed in sulfur-oxidation intermediates like tetrathionate and thiosulfate. While these data supports the influence of core microbial community members on a hyperalkaline spring’s geochemistry, there is also evidence that subsurface processes affect geochemistry and may impact community dynamics as well. Though the physiology and ecology of these astrobiologically relevant ecosystems are still being uncovered, this work helps identify a stable microbial community that impacts spring geochemistry in ways not previously observed in serpentinizing ecosystems.